Fermentation of Apple Juice with a Selected Yeast Strain Isolated from the Fermented Foods of Himalayan Regions and Its Organoleptic Properties - Kanwar, S. S.; Keshani, (Frontiers in Microbiology, 2016)
Twenty-three Saccharomyces cerevisiae strains isolated from different fermented foods of Western Himalayas have been studied for strain level and functional diversity in our department. Among these 23 strains, 10 S. cerevisiae strains on the basis of variation in their brewing traits were selected to study their organoleptic effect at gene level by targeting ATF1 gene, which is responsible for ester synthesis during fermentation. Significant variation was observed in ATF1 gene sequences, suggesting differences in aroma and flavor of their brewing products. Apple is a predominant fruit in Himachal Pradesh and apple cider is one of the most popular drinks all around the world hence, it was chosen for sensory evaluation of six selected yeast strains. Organoleptic studies and sensory analysis suggested Sc21 and Sc01 as best indigenous strains for soft and hard cider, respectively, indicating their potential in enriching the local products with enhanced quality.